Quantification Of Three-Dimensional Elastic-Plastic Crack-Tip Stress Fields - Yusoff, Norwahida (2018)
Conventional structural integrity assessments are formulated based on plane strain fracture toughness to provide a conservative estimate of failure. However, such approach often leads to unnecessary repair and shutdown of structures. This conservatism has been minimized by the two-parameter fracture mechanics J − T/Q. However, the J − T/Q approach is incapable of quantifying three-dimensional cracktip constraint loss that leads to the emergence of new three-dimensional techniques in fracture mechanics.